The beautiful people : a novel - Gable, Michelle (Graydon House, 2024)
"It's 1961, and for Margo Hightower, everything is about to change. True, her engagement is off, her family has fallen in scandal, and she's completely broke. But she's just been hired as an assistant to photographer Slim Aarons--famous for his vibrant pictures of high society, royalty, and Hollywood stars--and she knows this opportunity is her ticket to something better. From the bright beaches of Acapulco to glitzy parties in New York, Margo is thrown headfirst into the glamorous jet-set world she so covets, observing its ways from behind the camera as Slim's sidekick. There's Jackie Kennedy, Truman Capote and his Swans, a host of Vanderbilts. Beautiful people in beautiful places. But when they land in Palm Beach, a scene with few rules and many riches, the lines between work and play begin to blur. As Margo becomes swept up in the city's social circle--and into a friendship with heiress and rising fashion designer Lilly Pulitzer--the golden life seems increasingly in reach. Until she finds herself entangeled in a complicated web of loyalties and secrets that could bring it all crashing down..." --